(untitled) (European Bison Conservation Newsletter, 2009)
The author has analyzed reports of dissecting carcasses of animals and certificates on deaths of 128 bison from 1960 to 2008. The highest death rate is observed among bison being about one year old (57%). Themortality rate within a year occurs unevenly. In summer, autumn and winter there is an increase of this factor. Causes of animals’ death in the breeding station have been classified according to the groups: traumas, diseases of different organs, invasion and infectious diseases. The main cause of animals’ death are traumas – 43.7%. Helminthosis, problems of digestive apparatus and poisoning are on the second place among the death reasons. Bison under one year die of traumas, still birth, breakage of an umbilical cord, and absence of mother’s milk.